2000
DOI: 10.1348/026151000165779
|View full text |Cite
|
Sign up to set email alerts
|

The diachronic approach and solutions to interpersonal conflicts

Abstract: The diachronic approach consists of considering a phenomenon as a stage in an evolutive process. The authors postulate that this approach plays a role at the level of everyday thinking in the discovery of solutions to problems. The present experiment aims at studying the relationships between levels of the diachronic approach in children and their ability to imagine solutions to a conflict between children. Sixty children aged 8 to 12 years were presented first with tasks assessing their level of diachronic te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 0 publications
5
15
0
Order By: Relevance
“…It has been suggested that difficulties in ''time travel'' are characteristic of autism (Suddendorf & Corballis, 1997), indeed Boucher (1999) suggests that this deficit may be, in part, a causal factor since an inability to represent temporal experience would impair a continuing sense and understanding of self and others. The findings here support this proposition and are in line with Montangero et al (2000) who have found this ability to be positively related to conflict resolution in children. Channon et al (2001) suggest that the problemsolving difficulties faced by individuals with Asperger syndrome may be a result of limited knowledge stores of prior problem solutions or due to problems in accessing prior knowledge.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It has been suggested that difficulties in ''time travel'' are characteristic of autism (Suddendorf & Corballis, 1997), indeed Boucher (1999) suggests that this deficit may be, in part, a causal factor since an inability to represent temporal experience would impair a continuing sense and understanding of self and others. The findings here support this proposition and are in line with Montangero et al (2000) who have found this ability to be positively related to conflict resolution in children. Channon et al (2001) suggest that the problemsolving difficulties faced by individuals with Asperger syndrome may be a result of limited knowledge stores of prior problem solutions or due to problems in accessing prior knowledge.…”
Section: Discussionsupporting
confidence: 91%
“…The attempt here was to capture some element of the ability to adopt a diachronic approach (cf. Montangero, Pons, & Cattin, 2000) where actions are inserted within a time period rather than just considered in the here and now.…”
Section: Autobiographical Memory Cueing Taskmentioning
confidence: 99%
“…The materials used in the study were identical to those used in previous studies of diachronic thinking in typically developing children (Maurice-Naville & Montangero & Parrat-Dayan, 1992;Tryphon & Montangero, 1992; a Raw scores of 29 and 27 convert to age equivalents of 9;9 and 9;3, respectively; scores of 26 and 24 convert to age equivalents of 9;00 and 8;06 b Raw scores of 90 and 88 convert to age equivalents of 8;10 and 8;8, respectively, scores of 83 and 90 convert to age equivalents of 8;01 and 8;10 1995; Montangero et al, 1996Montangero et al, , 2000Pons & Montangero, 1999;. The procedures were also closely similar.…”
Section: General Points Of Proceduresmentioning
confidence: 99%
“…In typically developing children, Tendency develops slowly but steadily between the ages of 7;0 and 12;0 years. Thus, a majority of 7;0 years old describe an object or situation only as it is at the present moment, whereas most 12;0-year-old children make reference to past and/or future states of the object or situation (Montangero & ParratDayan, 1992;Montangero & Pons, 1995;Montangero, Pons, & Cattin, 2000;Pons, Montangero, Quadir, & Bazan, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation